On the Keyhole Hypothesis: High Mutual Information between Ear and Scalp EEG - Mikkelsen, Kaare B.; Kidmose, Preben; Hansen, Lars K. (Frontiers in Human Neuroscience, 2017)
We propose and test the keyhole hypothesis - that measurements from low dimensional EEG such as ear-EEG reflect a broadly distributed set of neural processes. We formulate the keyhole hypothesis in information theoretical terms. The experimental investigation is based on legacy data consisting of 10 subjects exposed to a battery of stimuli, including alpha-attenuation, auditory onset and mismatch-negativity responses and a new medium-long EEG experiment involving data acquisition during 13 hours. Linear models were estimated to lower bound the scalp-to-ear capacity, i.e., predicting ear-EEG data from simultaneously recorded scalp EEG. A cross-validation procedure was employed to ensure unbiased estimates. We present several pieces of evidence in support of the keyhole hypothesis: There is a high mutual information between data acquired at scalp electrodes and through the ear-EEG "keyhole", furthermore we show that the view - represented as a linear mapping - is stable across both time and mental states. Specifically, we find that ear-EEG data can be predicted reliably from scalp EEG. We also address the reverse view, and demonstrate that large portions of the scalp EEG can be predicted from ear-EEG, with the highest predictability achieved in the temporal regions and when using ear-EEG electrodes with a common reference electrode.